Dynamic co-catalysis of Au single atoms and nanoporous Au for methane pyrolysis - Wei Xi (Nature Portfolio, 2020)
Nanocatalysts and single‐atom catalysts are generally considered as two categories with distinct performances. Here, in situ TEM study of catalytic methane pyrolysis over nanoporous Au reveals a highly dynamic process where co‐catalysis exists among various catalyst forms.